Using NMR to Study the Process of Rigid Polyurethane Depolymerization - Maioli, Juliana Proliciano; Soares, João Vitor Oliveira; Uliana, Fabricio; Valim, Thays Cardoso; Francisco, Carla Santana; da Silva Filho, Eloi Alves; Lacerda Junior, Valdemar; Cunha Neto, Alvaro (Orbital: The Electronic Journal of Chemistry, 2019)
Polyurethanes (PUs) have been widely used in several trade sections. Thereby, large amounts of waste are produced and need to be correctly disposed of. Research on this theme has been helping industries to apply recycling processes that are cheap and efficient. In this work, the glycolysis of a rigid PU was performed using different catalysts. 1H NMR analysis was used to obtain the rate of PU depolymerization. Glycerol (GCL) and diethylene glycol (DEG) were tested as glycolysis agents. The PU was synthesized to be free of additives in the depolymerization process, and its characterization was performed using FTIR and 1H NMR analyses. The use of NaOH as a catalyst showed a better conversion rate, as is already known in the literature. Ionic liquids (LIs) also presented good results, which can be improved by modifying the reaction conditions. To determine the composition of the mixture of products in the depolymerization reaction, diffusion ordered spectroscopy 1H NMR (DOSY-NMR) was used. DOSY-NMR indicated a complex mixture of reaction by-products, differently from the 1H NMR data, which indicated the formation of a simple diamine-terminated by-product. DOI: http://dx.doi.org/10.17807/orbital.v11i1.1385